INTERPERSONAL ATTRACTION THROUGH THE PRISM OF VOCATIONAL PEDAGOGIC COMMUNICATION - LIVITSKA , Nataliia; RUDYNSKYI, Vitlalii (ГУМАНІТАРНІ СТУДІЇ : ІСТОРІЯ ТА ПЕДАГОГІКА, 2022)
The article considers the phenomenon of interpersonal attraction in the projection of Vocational Pedagogic Communication between lecturer and student. Particular attention is paid to the internal factors of pedagogical attraction and their constitutive manifestations, including: expressive speech, communicative flexibility and expediency, professional erudition, creative uniqueness, personal position and others. In addition, the idea of “attractive lecturer” is emphasized. One of his important features is ability to “communicative diplomacy”, which is manifested in sectioning of appropriate content of messages, adequately responding to various changes in communicative models. Among the professional tasks of a teacher is to create a favorable background for interpersonal attraction. Its emergence in vocational communication depends on many factors that may be both external to the subject and object of communication (external attractiveness, appearance, facial expressions, gestures, the communication situation, environment) and internal (intrinsic qualities of subject and object, such as communication style, distinctive imagination, subjective ethical principles). Interpersonal attraction of participants in communicative dialogue is usually formed at the initial stage of professional communication – modelling future relationships in preparation for the learning process. That is why the aesthetics of the teacher's self-expression in the first minutes of acquaintance should express an attractive character. The level of recipient’s mood in relation to the communicator (lecturer) may be different. Accordingly, we believe that it is possible to record an increase/decrease in the degree of interpersonal attraction. In the process of establishing contacts of interpersonal attraction is the acceptance or rejection of communicative models of the interlocutor, their understanding and comparison in accordance with their own norms and rules of worldview and understanding of the importance of the teacher as a whole. Interpersonal interaction of educators with students should be based on the principles of equality, mutual respect, trust and morality, accompanied by systematic use in the educational process of the necessary formulas of etiquette and culture of speech.